PENGATURAN MENGENAI LAPORAN HARTA KEKAYAAN PENYELENGGARA NEGARA DALAM UPAYA PENCEGAHAN TINDAK PIDANA KORUPSI DI INDONESIA - Nyoman Toya; I Wayan Putu Sucana Aryana; Cokorda Istri Dian Laksmi Dewi (Jurnal Komunikasi Hukum, 2024)
Compliance with reporting the assets of state administrators continues to increase. However, LHKPN accountability is still low. This study aims to find out and analyze (1) the arrangements regarding the Wealth Report of State Administrators in the prevention of criminal acts of corruption in Laws and Regulations, and (2) analyze the obstacles to the mechanism of Reporting of State Officials' Wealth as an effort to prevent criminal acts of corruption. The type of research used is normative legal research. The data obtained from this study were secondary data obtained through a literature study, then the data obtained were analyzed qualitatively through a statutory and conceptual approach. The results of this study indicate that (1) arrangements regarding LHKPN are regulated in several regulations, including Law Number 28 of 1999 concerning State Administrators who are Clean and Free from Corruption, Collusion and Nepotism; Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission; and Corruption Eradication Commission Regulation Number 7 of 2016 concerning Procedures for Registration, Announcement and Examination of Reports on State Administration Assets. (2) the indecision of sanctions regarding LHKPN and without being balanced with the norms of authority of the implementing agency. Administrative sanctions in the LHKPN mechanism are considered to be not running optimally and seem useless. So that efforts need to be made regarding the importance of other sanctions that can provide a deterrent effect for perpetrators, namely criminal sanctions in the implementation of State Officials Wealth Reports.